2004
DOI: 10.1111/j.1467-9566.2004.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Moving forward? Complementary and alternative practitioners seeking self‐regulation

Abstract: Complementary and alternative medicine (CAM) occupationscontinue to struggle towards achieving professional status, especially in the form of statutory regulation. Many consider professional status a worthwhile goal for CAM occupations, yet it is a process fraught with tensions. In this paper we present in-depth interview data from the leaders of three CAM groups (naturopaths, traditional Chinese medicine practitioners acupuncturists, and homeopaths) in Ontario, Canada that demonstrate four main strategies use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 23 publications
0
79
1
1
Order By: Relevance
“…All groups other than GPs employed a broadly similar expertise discourse, similar to that reported in Leonard's (2003) study. This, however, contrasts somewhat with the findings of earlier studies by Foley and Faircloth (2003) and Welsh et al (2004) discussed above; none of our respondents sought to legitimise their occupation in terms of a more overarching discourse of 'science'. The organisational efficiency discourse was employed only by our nurses and focused on claims that the specialist heart failure nursing role occupied a niche between the specialist work of cardiologists and the ongoing responsibility of GPs.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…All groups other than GPs employed a broadly similar expertise discourse, similar to that reported in Leonard's (2003) study. This, however, contrasts somewhat with the findings of earlier studies by Foley and Faircloth (2003) and Welsh et al (2004) discussed above; none of our respondents sought to legitimise their occupation in terms of a more overarching discourse of 'science'. The organisational efficiency discourse was employed only by our nurses and focused on claims that the specialist heart failure nursing role occupied a niche between the specialist work of cardiologists and the ongoing responsibility of GPs.…”
Section: Discussioncontrasting
confidence: 56%
“…A number of empirical studies have examined the content of legitimation discourses, focusing mainly on interprofessional relationships in the context of practitioners of complementary and alternative medicine (Mizrachi et al 2005, Welsh et al 2004, Norris 2001, the nursing or midwifery boundary with medicine (Foley andFaircloth 2003, Leonard 2003) and the theatre nurse relationship to operating department practitioners (Timmons and Tanner 2004). Such research has suggested a number of recurring themes across a range of countries and of conventional and complementary health professions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western trained acupuncturists, on the other hand, declared that traditional training and education lacked the evidence-based scientific approach found in western medicine (Welsh et al 2004). Eventually, during the drafting of Bill 50, the government was able to serve as a mediator in order to give enough credibility to both forms of practice (The Canadian Press 2013).…”
Section: History and Contextmentioning
confidence: 99%
“…Although TCM/A groups in Ontario had a history of lobbying for self-regulating status (Gilmour, Kelner, Wellman 2002;Welsh et al 2004), and various provincial governments had considered the issue since the 1990s, it was the timing of a combination of factors that gave the issue sufficient momentum to stay on the government's policy agenda long enough for action to be taken.…”
Section: How and Why The Reform Came To Passmentioning
confidence: 99%